2017
DOI: 10.1177/1049732317739839
|View full text |Cite
|
Sign up to set email alerts
|

The Experience of Persons With Hematological Malignancy When Communicating With Health Care Professionals

Abstract: This study aimed to elucidate the experiences of Japanese persons with hematological malignancy (PHMs) in communicating with health care professionals (HCPs), from diagnosis to the end of life, as recalled by their families. We interviewed 14 bereaved families and analyzed the data using the basic techniques of grounded theory. We found that PHMs lived to the fullest possible when they experienced ownership of their illness process despite their disease. The ownership was made possible by active communication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
(60 reference statements)
1
1
0
Order By: Relevance
“…33 Our results have indicated that some participants felt disconnected from their physician or care team, which affected their overall satisfaction and cancer experience. This corresponds to previous studies that reviewed patients' communication needs and satisfaction with their providers, 37 in particular, the lack of communication about the emotional needs of patients. 38 Cultural differences can also result in difficulties with communication between cancer care teams and rural patients.…”
Section: Discussionsupporting
confidence: 85%
“…33 Our results have indicated that some participants felt disconnected from their physician or care team, which affected their overall satisfaction and cancer experience. This corresponds to previous studies that reviewed patients' communication needs and satisfaction with their providers, 37 in particular, the lack of communication about the emotional needs of patients. 38 Cultural differences can also result in difficulties with communication between cancer care teams and rural patients.…”
Section: Discussionsupporting
confidence: 85%
“…This finding seemed unexpected, since malignancy was reported as a risk factor of VTE. However, it might be attributed to patients with malignancy often receiving more attention from medical staff, and they may also have received more preventive treatments [67]. In addition, studies with a higher percentage of males (B = −0.00984, z = −4.08) had a lower prevalence of VTE.…”
Section: Discussionmentioning
confidence: 99%